Antecedents of raciality in Cuba. Current behavior (Islas, 2022)
Introduction: The present work has like center the analysis of the racialidad in Cuba, its historical antecedents, its current behavior and the actions to face the racist and discriminatory feelings that still exist in the Cuban society.Methods: It is a qualitative analysis, the analysis of document and bibliography; the historical-logical one and the inductive one are as methods - deductive to approach the origin and evolution of the racialidad in Cuba.  Results: The article is good of relating for other studies on the topic, it emphasizes about the danger that represents the racism and racist attitudes for Cuba and it denounces the interest of the governments from the United States in being able to divide the Cuban town through the racial conflict.  Conclutions: The article highlights that the racism and the racial discrimination in Cuba have roots in it’s to become historical, at the present time it is influenced by the changes in the economy, the technological development of the communications and the right governments.  He/she stands out the idea of the elimination of all vestige of racism.
Keywords: raciality; racism; racial discrimination; Cuba.